Coding activities in early childhood: a systematic review - Ugras, Mustafa; Gunes, Habibe; Ugras, Hilal; Papadakis, Stamatios; Kalogiannakis, Michail (Inderscience Enterprises Ltd, 2025)
The current study aims to systematically review the literature on teaching basic coding skills in early childhood education, particularly for children aged 3 to 8 years. A systematic literature review was conducted of 45 articles published in Science Direct, Wiley Online Library, SpringerLink, Sage Journals, Taylor & Francis Online, ERIC, JSTOR and Google Scholar on using coding activities in the preschool years from 2014-2023. The review presents empirical research with young learners and reports on relevant frameworks and curricula, the impact of pedagogical approaches and tools on learning, and the learning outcomes and pedagogical benefits of teaching coding. Plugged and unplugged coding activities can be introduced to young learners as a stand-alone subject or integrated into the regular kindergarten curriculum based on the studies reviewed. Additionally, coding can be incorporated into literacy and storytelling activities as a developmentally appropriate approach. The authors conclude that for educators to become competent in introducing coding activities into early childhood education, future research should focus on developing curricula that fully integrate coding and accompanying teacher training programmes.
Keywords: early childhood education; ECE; coding skills; computational thinking; CT; robotics; systematic literature review; PRISMA